Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17041335
|View full text |Cite
|
Sign up to set email alerts
|

Early Discharged Lumbar Spine Fusion Reduced Postoperative Readmissions: A Retrospective Cohort Study

Abstract: Early discharge (ED) has emerged and gained popularity in spine surgery. However, the benefits of ED in lumbar fusion have not yet been validated by large cohort studies. To evaluate the effects of ED on readmissions and reoperations in lumbar fusion, this study utilized a national database to enroll patients who had undergone lumbar fusion surgery at age 50–70 years, and grouped them into an ED group or a comparison group. In the comprehensive follow-up of 180 days post-operation, the two groups were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…27-29 Huang et al described the clinical relevance of early discharges following lumbar fusions. 30 They found that an early discharge within 3 days of admission could yield up to a 25% reduced risk of readmission for any cause within 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…27-29 Huang et al described the clinical relevance of early discharges following lumbar fusions. 30 They found that an early discharge within 3 days of admission could yield up to a 25% reduced risk of readmission for any cause within 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%